Exploratory study on calibrating the politeness factor of MOBIL - Pacson, Jemuel S.; Taguiam, Jebus Edrei C.; Palmiano, Hilario Sean O. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
The main purpose of this study is to explore methods in calibrating MOBIL parameters for Philippine drivers by using observed trajectories in the country. It aims to find the significant trends in frequencies of parameter values among lane-changing drivers which may lead to calibrating the parameters. A video footage of a midblock along Katipunan Avenue was captured and corrected. Through a video analysis software, Tracker, the lateral and longitudinal trajectory of the lane-changing vehicle, its old follower and new follower extracted. The accelerations of the vehicles were then computed using a central difference acceleration formula. Since the accelerations were and unrealistically spiky, the data sets were smoothed using sEMA. The accuracy of Tracker was validated by comparing the acceleration values computed using GPS trajectories with the sEMA-smoothed Tracker trajectories. The MOBIL criteria of safety and incentive were assessed. All observed events were found to be within the safe deceleration and the incentive criterion is described by an inequality. Hence, the politeness factor values computed were limits of the inequality.These limits were categorized as either lower bounds or upper bounds and were further classified into four cases describing the behavior of the drivers. The lane changes were also classified as either discretionary or mandatory lang change. The frequency distributions for the different categories and cases of P limits were plotted. As further exploration, Tukey's Boxplot Method was applied to the P limits to determine the trends of the concentration of the limits.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Automobile driving -- Lane changing; Traffic flow -- Mathematical models